The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00432-007-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

Palliative gastrectomy and chemotherapy for stage IV gastric cancer

Abstract: The survival time and palliative duration were significantly longer in patients after PG than after non-resection operations. Postoperative chemotherapy prolonged the survival time of patients after palliative surgery. PG combined with adjuvant chemotherapy may improve survival in patients with stage IV gastric cancer, even with liver metastasis, peritoneal dissemination, and lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 21 publications
3
60
0
9
Order By: Relevance
“…A recent meta-analysis of randomized trials that compared chemotherapy and best supportive care in patients with MGC revealed that chemotherapy was more beneficial than best supportive care alone with respect to OS and quality of life [20]. However, the role of surgery (debulking gastrectomy or gastrectomy plus metastasectomy) in GC patients with distant metastasis is still controversial [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The results of our study suggest that surgery may be beneficial in MGC patients when combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent meta-analysis of randomized trials that compared chemotherapy and best supportive care in patients with MGC revealed that chemotherapy was more beneficial than best supportive care alone with respect to OS and quality of life [20]. However, the role of surgery (debulking gastrectomy or gastrectomy plus metastasectomy) in GC patients with distant metastasis is still controversial [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The results of our study suggest that surgery may be beneficial in MGC patients when combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although systemic chemotherapy is the only proven standard treatment of MGC [19], most previous studies evaluating the benefit of gastrectomy ± metastasectomy in MGC were performed without considering the influence of chemotherapy. In most previous studies [3][4][5][6][8][9][10][11][12][13][14][15][16][17][18], both patients who had and had not received systemic chemotherapy were included. Therefore, many clinicians have been confused about the results, insisting on the benefits of surgery in stage IV (M 1 ) GC, based on results derived from heterogeneous patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations